Production potential of Eucalypt woodlots for bioenergy in the Winelands region of the Western Cape - Botman, Ilse (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2010.